Uncertainty of climate models and policy implications: A European perspective - Alfred Greiner (Bielefeld University, Faculty of Business Administration and Economics, 2024)
In this paper we show that both climate models and economic models studying the effects of climate change are characterized by high uncertainty. Hence, far reaching policy implications such as the net zero goal lack a definite scientific foundation. Neverthelss, it cannot be excluded that the continued global warming will go along with high damages in the future. Therefore, decreasing greenhouse gas emissions could be justified due to the precautionary motif. However, there are strong signals from non-European economic regions that they definitely put a higher weight on economic growth rather than on greenhouse gas mitigation. Since reductions in the European Union cause tremendous costs without influencing the climate on earth, the net zero goal of the New Green Deal of the European Union is to be seen sceptical.
urn:nbn:de:0070-pub-29886730
Keywords: Q54; Q58; 330; Climate models; uncertainty; economic policy